A circularly polarized implantable rectenna for self-charging pacemaker. Issue 11 (24th July 2022) - Saha, Pujayita; Mitra, Debasis; Parui, Susanta Kumar
Abstract : Pacemakers have existed for years for patients with heart failure to re-establish cardiac electrical pulses. However, the main complication related to a traditional pacemaker is its limited battery life. To circumvent such problems, wireless battery charging technology is one of the emergent applications for cardiac pacing. In this paper, an implantable rectenna, consisting of a circularly polarized (CP) monopole antenna, matching circuit and a rectifier, is proposed for pacemaker battery charging. To reduce the impedance mismatch loss, the matching network is incorporated between the antenna and the rectifier. A pair of T-shaped slots are introduced in the ground plane of the antenna to achieve the desired CP operation. The resonant frequency of the rectenna is 2.45 GHz with an impedance bandwidth of 28.45% and 5.73% 3 dB AR bandwidth. At −10 dBm input power, the rectenna output is 0.3 V with a rectenna efficiency of 41%.